PVDF-PMMA (Polyvinylidene Fluoride-Polymethyl Methacrylate) based polymer electrolyte membrane as well as preparation method and application thereof
By adding PMMA, lithium salt, active fillers and phosphine compounds to PVDF, the problem of low conductivity of PVDF-based solid polymer electrolyte membrane is solved, and a PVDF-PMMA-based polymer electrolyte membrane with high conductivity and long cycle time is achieved.
Patent Information
- Application Number
- CN202411864135.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
AI Technical Summary
The existing polyvinylidene fluoride (PVDF)-based solid polymer electrolyte membrane has a low ionic conductivity, which limits its practical application in lithium batteries.
By adding PMMA, lithium salt, active filler and phosphine compounds to PVDF, their conductivity is adjusted, and the conductivity of the film is improved through the film formation process.
The conductivity of the PVDF-PMMA-based polymer electrolyte membrane is significantly improved, the circulation time of lithium symmetric batteries is extended, and the mechanical strength of the membrane is improved.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium batteries, and in particular to a PVDF-PMMA-based polymer electrolyte membrane and a preparation method and application thereof. Background Art
[0002] In polymer ion batteries, polymer electrolyte membrane is the key material of polymer ion batteries. As the separator and electrolyte of ion batteries, polymer electrolyte membrane should have high room temperature ionic conductivity, good electrode interface stability, wide electrochemical window and good mechanical properties.
[0003] Currently, polymer electrolyte membranes can be divided into three types: liquid polymer electrolyte membranes, pure solid polymer electrolyte membranes and gel-type polymer electrolyte membranes. Among them, solid electrolyte membranes are an important component of solid-state ion batteries. Due to the soft nature of polymers and high feasibility of large-scale manufacturing, polymer-based solid electrolyte membranes have received extensive attention and research.
[0004] Polyvinylidene fluoride (PVDF) is a common polymer matrix in solid polymer electrolytes, but the low ionic conductivity of PVDF-based polymer electrolyte membranes hinders their further practical application. Summary of the invention
[0005] The invention provides a PVDF-PMMA-based polymer electrolyte membrane and a preparation method and application thereof. The PVDF-PMMA-based polymer electrolyte membrane provided by the invention has high electrical conductivity.
[0006] The present invention provides a PVDF-PMMA-based polymer electrolyte membrane, comprising the following components: PVDF, PMMA, lithium salt, active filler and phosphine compound;
[0007] The mass ratio of the PVDF to the lithium salt is (2-15):1;
[0008] The mass ratio of PVDF to PMMA is (1-10):1;
[0009] The mass ratio of the total mass of the PVDF and the lithium salt to the mass of the active filler is (2-30):1;
[0010] The mass ratio of the total mass of the PVDF and the lithium salt to the mass ratio of the phosphine compound is (5-30):1.
[0011] Preferably, the lithium salt includes one or more of LiFSI, LiTFSI, LiBOB, LiODFB, LiBF4, LiPO2F2 and LiAsF6.
[0012] Preferably, the active filler includes lithium element.
[0013] Preferably, the active filler includes one or more of lithium lanthanum zirconium tantalum oxide, lithium indium chloride, lithium yttrium chloride, lithium zirconium chloride, lithium tantalum chloride, lithium aluminum titanium phosphide, lithium aluminum germanium phosphate, lithium aluminum germanium phosphide and lithium phosphorus sulfur chlorine.
[0014] Preferably, the phosphine compound includes one or more of (SP,SP)-1,1'-bis{bis[3,5-bis(trifluoromethyl)phenyl]phosphino}-2,2'-bis[(R)-α-(dimethylamino)benzyl]ferrocene, 2-(dicyclohexylphosphine)-1-phenylindole, 1,2-bis(dimethylphosphino)ethane, vinyl chlorophosphate, 2-(di-tert-butylphosphine)-1-phenylpyrrole, n-pentyltriphenylphosphonium bromide, diphenylphosphoryl azide, 2-(di-tert-butylphosphine)-1,1'-binaphthyl, decafluorotriphenylphosphine, dihydrodiphenylphosphophenyl-4-isopropoxazole, R-binaphthol phosphate, 2-(diphenylhydroxyphosphinyl)ethyltriethoxysilane, 1-propylphosphoric acid cyclic anhydride, S-binaphthol phosphate, 1,1'-di-tert-butyldiphosphine and diethyl cyanophosphate.
[0015] The present invention also provides a method for preparing the PVDF-PMMA-based polymer electrolyte membrane described in the above technical solution, comprising the following steps:
[0016] The PVDF, PMMA, lithium salt, active filler, phosphine compound and organic solvent are mixed and then formed into a film to obtain the PVDF-PMMA based polymer electrolyte membrane.
[0017] Preferably, the organic solvent includes one or more of acetonitrile, dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide.
[0018] Preferably, the mixing temperature is 20 to 150° C. and the mixing time is 8 to 60 hours.
[0019] Preferably, the film forming comprises: casting and casting the mixed mixture and then drying it.
[0020] The present invention also provides the use of the PVDF-PMMA-based polymer electrolyte membrane described in the above technical solution or the PVDF-PMMA-based polymer electrolyte membrane prepared by the preparation method described in the above technical solution in a battery.
[0021] Phosphine compounds have high polarity and can promote the dissociation of lithium salts, thereby promoting rapid and efficient transmission of lithium ions in PVDF-PMMA-based polymer electrolyte membranes at room temperature, thereby improving the conductivity of PVDF-PMMA-based polymer electrolyte membranes.
[0022] Greatly improve the critical current density of polyvinylidene fluoride (PVDF) organic-inorganic composite solid electrolyte and greatly extend the cycle time of lithium symmetric batteries. DETAILED DESCRIPTION
[0023] The present invention provides a PVDF-PMMA-based polymer electrolyte membrane, comprising the following components: PVDF, PMMA, lithium salt, active filler and phosphine compound;
[0024] The mass ratio of the PVDF to the lithium salt is (2-15):1;
[0025] The mass ratio of PVDF to PMMA is (1-10):1;
[0026] The mass ratio of the total mass of the PVDF and the lithium salt to the mass of the active filler is (2-30):1;
[0027] The mass ratio of the total mass of the PVDF and the lithium salt to the mass ratio of the phosphine compound is (5-30):1.
[0028] In the present invention, the mass ratio of the PVDF to the lithium salt is (2-15):1. In a specific embodiment of the present invention, the mass ratio of the PVDF to the lithium salt may be 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1 or 15:1; the lithium salt preferably includes one or more of LiFSI, LiTFSI, LiBOB, LiODFB, LiBF4, LiPO2F2 and LiAsF6.
[0029] In the present invention, the mass ratio of PVDF to PMMA is (1-10):1. In a specific embodiment of the present invention, the mass ratio of PVDF to PMMA can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1.
[0030] The conductivity of PVDF can be adjusted by adding lithium salt and PMMA, and lithium salt and PMMA can improve the interface compatibility of the composite solid electrolyte and increase its critical current density.
[0031] In the present invention, the mass ratio of the total mass of the PVDF and the lithium salt to the active filler is (2-30):1. In a specific embodiment of the present invention, the mass ratio of the total mass of the PVDF and the lithium salt to the active filler can be 2:1, 5:1, 10:1, 15:1, 20:1, 25:1 or 30:1; the active filler preferably includes lithium; the active filler preferably includes lithium lanthanum zirconium tantalum oxide (Li 6.5 Ln3Z 1.5 Ta 0.5O 12 ,LLZTO), lithium indium chloride (Li3InCl6), lithium yttrium chloride (Li3YCl6), lithium zirconium chloride (Li2ZrCl6), lithium tantalum chloride (LiTaCl6), lithium aluminum titanium phosphide (LATP), lithium aluminum germanium phosphate (LAGP), lithium aluminum germanium phosphide (LAGP) and lithium phosphorus sulfur chloride (LPSCl). Active fillers can improve interface properties.
[0032] In the present invention, the mass ratio of the total mass of the PVDF and the lithium salt to the mass ratio of the phosphine compound is (5-30):1. In a specific embodiment of the present invention, the mass ratio of the total mass of the PVDF and the lithium salt to the phosphine compound can be 5:1, 10:1, 15:1, 20:1, 25:1 or 30:1; the phosphine compound preferably includes (SP,SP)-1,1'-bis{bis[3,5-bis(trifluoromethyl)phenyl]phosphino}-2,2'-bis[(R)-α-(dimethylamino)benzyl]ferrocene, 2-(bicyclo One or more of 2-(di-tert-butylphosphine)-1-phenylindole, 1,2-bis(dimethylphosphino)ethane, vinyl chlorophosphate, 2-(di-tert-butylphosphine)-1-phenylpyrrole, n-pentyltriphenylphosphonium bromide, diphenylphosphoryl azide, 2-(di-tert-butylphosphine)-1,1'-binaphthyl, decafluorotriphenylphosphine, dihydrodiphenylphosphine-4-isopropoxazole, R-binaphthol phosphate, 2-(diphenylhydroxyphosphinyl)ethyltriethoxysilane, 1-propylphosphoric acid cyclic anhydride, S-binaphthol phosphate, 1,1'-di-tert-butyldiphosphine and diethyl cyanophosphate. Phosphine compounds can improve interface properties.
[0033] Lithium salts and phosphine compounds can improve the mechanical strength of PVDF-PMMA-based polymer electrolyte membranes.
[0034] The present invention also provides a method for preparing the PVDF-PMMA-based polymer electrolyte membrane described in the above technical solution, comprising the following steps:
[0035] The PVDF, PMMA, lithium salt, active filler, phosphine compound and organic solvent are mixed and then formed into a film to obtain the PVDF-PMMA based polymer electrolyte membrane.
[0036] In the present invention, the organic solvent preferably includes one or more of acetonitrile, dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide.
[0037] In the present invention, the mixing temperature is preferably 20-150°C, and the time is preferably 8-60h; in a specific embodiment of the present invention, the mixing temperature can be 20°C, 30°C, 50°C, 70°C, 80°C, 90°C, 110°C, 130°C or 150°C, and the time can be 8h, 16h, 24h, 30h, 36h, 40h, 45h, 50h or 60h.
[0038] In the present invention, the film forming preferably includes: casting and casting the mixed mixture and then drying it.
[0039] In the present invention, the drying temperature is preferably 20-100°C, and the time is preferably 2-48h; in a specific embodiment of the present invention, the drying temperature can be 20°C, 30°C, 50°C, 70°C, 80°C or 100°C, and the time can be 2h, 4h, 8h, 16h, 24h, 30h, 36h, 40h or 48h.
[0040] The present invention also provides the use of the PVDF-PMMA-based polymer electrolyte membrane described in the above technical solution or the PVDF-PMMA-based polymer electrolyte membrane prepared by the preparation method described in the above technical solution in a battery.
[0041] The PVDF-PMMA-based polymer electrolyte membrane provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0042] The number average molecular weight of PVDF used in the examples and comparative examples is 71,000; the number average molecular weight of PMMA is 300,000.
[0043] In the embodiments and comparative examples, stable cycling means that the voltage and capacity remain unchanged.
[0044] Example 1
[0045] 5 g PVDF, 2.5 g LiTFSI and 5 g PMMA were weighed respectively, and then 0.75 g LLZTO powder and 0.75 g (SP, S′P)-1,1′-bis{bis[3,5-bis(trifluoromethyl)phenyl]phosphino}-2,2′-bis[(R)-α-(dimethylamino)benzyl]ferrocene were added, and then DMSO was added. The mixture was heated and stirred at 45 °C for 36 h to obtain a uniformly mixed slurry, which was then cast on a polytetrafluoroethylene mold and vacuum dried at 75 °C for 20 h to obtain a PVDF-PMMA-based polymer electrolyte membrane with a thickness of 200 μm. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 1.7×10 -4 S / cm, its interfacial impedance is 547.4Ω, and its lithium symmetric half-cell is 0.2mAcm-2 The current density can be stably cycled for 50 h.
[0046] Example 2
[0047] 5 g PVDF, 1 g LiODFB and 2.5 g PMMA were weighed respectively, and then 0.2 g LATP powder and 1.2 g 2-(dicyclohexylphosphine)-1-phenylindole were added, and then DMF was added. The mixture was heated and stirred at 45 °C for 15 h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 80 °C for 12 h to obtain a PVDF-PMMA-based polymer electrolyte membrane with a thickness of 200 μm. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 4.7×10 -4 S / cm, its interfacial impedance is 498.7Ω, and its lithium symmetric half-cell is 0.2mAcm -2 The current density can be stably cycled for 78 hours.
[0048] Example 3
[0049] 7g PVDF, 1g LiBOB and 2g PMMA were weighed respectively, and then 4g LAGP powder and 0.27g 2-(dicyclohexylphosphine)-1-phenylindole were added, and then DMAC was added. The mixture was heated and stirred at 80°C for 8h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 70°C for 10h to obtain a PVDF-PMMA-based polymer electrolyte membrane with a thickness of 200μm. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 8.7×10 -4 S / cm, its interfacial impedance is 404.6Ω, and its lithium symmetric half-cell is 0.2mAcm -2 The current density can be stably cycled for 100 h.
[0050] Example 4
[0051] 9 g PVDF, 1 g LiFSI and 0.9 g PMMA were weighed respectively, and then 3 g Li3InCl6 powder and 0.5 g 2-(di-tert-butylphosphine)-1,1'-binaphthyl were added, and then acetonitrile was added. The mixture was heated and stirred at 70 °C for 12 h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 65 °C for 16 h to obtain a PVDF-PMMA-based polymer electrolyte membrane with a thickness of 200 μm. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 1.5×10 -3 S / cm, its interfacial impedance is 347.4Ω, and its lithium symmetric half-cell is 0.2mAcm -2 The current density can be stably cycled for 200 h.
[0052] Example 5
[0053] 12g PVDF, 1g LiBF4 and 4g PMMA were weighed respectively, and then 1.95g LPSCl powder and 1.95g dihydrodiphenylphosphinophenyl-4-isopropazole were added, and then DMAC was added. The mixture was heated and stirred at 55°C for 12h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 75°C for 10h to obtain a PVDF-PMMA-based polymer electrolyte membrane with a thickness of 200μm. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 3.7×10 -3 S / cm, its interfacial impedance is 287.1Ω, and its lithium symmetric half-cell is 0.2mAcm -2 The current density can be stably cycled for 300 h.
[0054] Comparative Example 1 (pure PVDF)
[0055] 12g PVDF and 1g LiBF4 were weighed respectively, and then 1.95g LPSCl powder and 1.95g dihydrodiphenylphosphinophenyl-4-isopropazole were added, and then DMAC was added. The mixture was heated and stirred at 55°C for 12h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 75°C for 10h to obtain a PVDF-based polymer electrolyte membrane with a thickness of 200μm. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 7.4×10 -5 S / cm, its interfacial impedance is 681.2Ω, and its lithium symmetric half-cell is 0.2mAcm -2 The current density can be stably cycled for 27 hours.
[0056] Comparative Example 1 (PEO system)
[0057] 12 g of polyethylene oxide (PEO, number average molecular weight of 60,000) and 1 g of LiBF4 were weighed respectively, and then 1.95 g of LPSCl powder and 1.95 g of dihydrodiphenylphosphinophenyl-4-isopropazole were added, and then DMAC was added. The mixture was heated and stirred at 55 °C for 12 h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 75 °C for 10 h to obtain a PEO-based polymer electrolyte membrane with a thickness of 200 μm. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 4.1×10 -6 S / cm, its interfacial impedance is 867.5Ω, and its lithium symmetric half-cell is 0.2mA cm -2 A short circuit occurs immediately at this current density.
[0058] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A PVDF-PMMA-based polymer electrolyte membrane, characterized in that: The invention comprises the following components: PVDF, PMMA, lithium salt, active filler and phosphine compound; The mass ratio of the PVDF to the lithium salt is (2-15):1; The mass ratio of PVDF to PMMA is (1-10):1; The mass ratio of the total mass of the PVDF and the lithium salt to the mass of the active filler is (2-30):1; The mass ratio of the total mass of the PVDF and the lithium salt to the mass ratio of the phosphine compound is (5-30):
1.
2. The PVDF-PMMA-based polymer electrolyte membrane according to claim 1, characterized in that: The lithium salt includes one or more of LiFSI, LiTFSI, LiBOB, LiODFB, LiBF4, LiPO2F2 and LiAsF6.
3. The PVDF-PMMA-based polymer electrolyte membrane according to claim 1, characterized in that: The active filler includes lithium element.
4. The PVDF-PMMA-based polymer electrolyte membrane according to claim 1 or 3, characterized in that: The active filler includes one or more of lithium lanthanum zirconium tantalum oxide, lithium indium chloride, lithium yttrium chloride, lithium zirconium chloride, lithium tantalum chloride, lithium aluminum titanium phosphide, lithium aluminum germanium phosphate, lithium aluminum germanium phosphide and lithium phosphorus sulfur chlorine.
5. The PVDF-PMMA-based polymer electrolyte membrane according to claim 1, characterized in that: The phosphine compound includes one or more of (SP,SP)-1,1'-bis{bis[3,5-bis(trifluoromethyl)phenyl]phosphino}-2,2'-bis[(R)-α-(dimethylamino)benzyl]ferrocene, 2-(dicyclohexylphosphine)-1-phenylindole, 1,2-bis(dimethylphosphino)ethane, vinyl chlorophosphate, 2-(di-tert-butylphosphine)-1-phenylpyrrole, n-pentyltriphenylphosphonium bromide, diphenylphosphoryl azide, 2-(di-tert-butylphosphine)-1,1'-binaphthyl, decafluorotriphenylphosphine, dihydrodiphenylphosphophenyl-4-isopropoxazole, R-binaphthol phosphate, 2-(diphenylhydroxyphosphinyl)ethyltriethoxysilane, 1-propylphosphoric acid cyclic anhydride, S-binaphthol phosphate, 1,1'-di-tert-butyldiphosphine and diethyl cyanophosphate.
6. The method for preparing the PVDF-PMMA-based polymer electrolyte membrane according to any one of claims 1 to 5, characterized in that: The following steps are involved: The PVDF, PMMA, lithium salt, active filler, phosphine compound and organic solvent are mixed and then formed into a film to obtain the PVDF-PMMA based polymer electrolyte membrane.
7. The preparation method according to claim 6, characterized in that: The organic solvent includes one or more of acetonitrile, dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide.
8. The preparation method according to claim 6, characterized in that: The mixing temperature is 20-150° C. and the mixing time is 8-60 hours.
9. The preparation method according to claim 6, characterized in that: The film forming comprises: casting and casting the mixed mixture and then drying it.
10. Use of the PVDF-PMMA-based polymer electrolyte membrane according to any one of claims 1 to 5 or the PVDF-PMMA-based polymer electrolyte membrane prepared by the preparation method according to any one of claims 6 to 9 in a battery.
Citation Information
Cited By
High-valued recovery method of PVDF / PMMA (Polyvinylidene Fluoride / Polymethyl Methacrylate) blended membrane based on selective precipitation of solvent
CN122213497A